Computational Design of Peptide Inhibitors Targeting the SARS-CoV-2 Main Protease - Das, Chainee; Mattaparthi, Venkata Satish Kumar (Coronaviruses, 2025)
BackgroundThe novel coronavirus disease also known as COVID-19 was first detected in December 2019 in Wuhan, China and was caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its effect can still be seen in some parts of the world due to the lack of effective antiviral drugs and vaccines for treatment and controlling the pandemic. Chymotrypsin-like protease (3CLpro), also known as the main protease (Mpro) of SARS-CoV-2 plays a vital role during its replication process of the pathogen’s lifecycle and is therefore considered a potential drug target for COVID-19. Hence, targeting the Mpro is an appealing approach for drug development because of its significant role in viral replication and transcription and therefore can act as an attractive drug target to combat COVID-19 as confirmed by researchers through numerous studies so far. Although small molecules dominate the field of drug market so far, peptide inhibitors still represent a class of promising candidates because of their similarity to endogenous ligands, high affinity, and low toxicity. It has been validated that therapeutic peptides can effectively and selectively inhibit the protein-protein interactions in viruses. Hence, it is necessary to design potential peptide inhibitors in order to inhibit the impact of the disease.ObjectiveTo design peptide inhibitors against the SARS-CoV-2 Main Protease using computational methods.MethodsThis study involves the development of potential target peptides that can act against the Mpro in a competitive mode against histone deacetylase (HDAC2) which had a high-confidence interaction with Mpro. Based on the interaction between Mpro and HDAC2, 13 peptides were designed out of which based on toxicity, binding affinity and binding site prediction, two peptides (peptide2 and peptide4) were screened and subjected to MD simulation.ResultsOur study shows that the two peptides bind to the active site of the Mpro and it attains a higher stability upon binding to the peptides. We also found out that the Mpro has a strong binding affinity with both the peptides (GBTOT = -72.85 kcal/mol for Mpro-peptide2 complex and GBTOT = -46.36 kcal/mol for the Mpro-peptide4 complex).ConclusionEven though declaring those peptides as future potent drug candidates would require more analysis and trials, our analysis will surely add value to the future findings and these findings could aid in the development of novel SARS-CoV-2 Mpro peptide inhibitors. These findings could aid in the development of novel SARS-CoV-2 Mpro peptide inhibitors.
Keywords: SARS-CoV-2